My wife is missing [large type] - Palmer, Daniel, 1962- (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"A family vacation turns into a nightmare for Michael Hart when he discovers his wife and two children have disappeared from their New York City hotel room. Horrified, he fears they've been kidnapped. Michael's frantic search to find them takes a shocking turn when he discovers that his wife, Natalie, appears to have left quite willingly, taking their children with her. The police want to know why. But there may be a reason why Natalie ran, something Michael can't tell the police--the truth about his past. While untangling his deceptions might be the key to locating Natalie, Michael knows it could also be his undoing. To find his wife, he must now turn to the one person capable of exposing all that he's been hiding"--